Effectiveness and Efficiency of the Use of the Workforce Training Program Budget at the North Sumatra Provincial Manpower Office - Novitayana Novitayana; Irawan Irawan (Journal of Research in Social Science and Humanities, 2025)
This study analyzes the effectiveness and efficiency of budget utilization for workforce training programs at the Manpower Office of North Sumatra Province using a qualitative approach. Although average budget realization reaches 90.60%, graduate employment absorption remains low at 38.9%–56.4%. Data were collected through in-depth interviews with budget officials, instructors, and trainees, as well as document reviews. Findings show that 78% of respondents consider budget implementation administratively compliant, but only 46% believe training materials match industry needs. Additionally, 63% identify limited facilities as the main obstacle to program effectiveness. The study suggests industry-based training planning, improved facilities, and stronger evaluations to optimize budget use